SELF-REGULATED LEARNING DURING COVID-19 PANDEMIC - Marindra Firmansyah; Dina Rahmi Daroini (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: The government implemented the regulation for higher education during the pandemic Covid-19 about the method of learning with an online system. This online learning model will affect self-regulated learning and academic achievement. Self-regulated learning for online learning has not been widely studied. Previous research has written that self-regulated learning in offline learning was formed by several factors. This research was conducted to find out that self-regulated learning and the factors that shape them are still relevant in online learning. The objectives of the study were to analyze the factors and relationships that influence self-regulated learning in online learning during the pandemic Covid-19.Methods: This research was conducted with confirmatory factor analysis (CFA) on the survey results of 175 respondents. The questionnaire consisted of 54 validated questions on the Likert scale. Calculations were done using PLS-SEM data analysis (Smart PLS version 3.0).Results: This study produces a good and strong model with a GoF value> 0.34. Path analysis shows that all O-sample values are positive with t statistic > 1.97 and p-value < 0.025. Thus, each factor has a significant positive effect on forming self-regulated learning.Conclusion: The factors that have been researched on offline learning that forming self-regulated learning are still relevant to use in online learning. These factors are mastery goal orientation, task value perception, academic self-efficacy, metacognitive knowledge awareness, prior learning experiences, good grades, employment prospects, successful future, support from teaching staff, peers, and family.